2013
DOI: 10.1073/pnas.1308950110
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors are neuroprotective and preserve NGF-mediated cell survival following traumatic brain injury

Abstract: Acute traumatic brain injury (TBI) is associated with long-term cognitive and behavioral dysfunction. In vivo studies have shown histone deacetylase inhibitors (HDACis) to be neuroprotective following TBI in rodent models. HDACis are intriguing candidates because they are capable of provoking widespread genetic changes and modulation of protein function. By using known HDACis and a unique small-molecule pan-HDACi (LB-205), we investigated the effects and mechanisms associated with HDACi-induced neuroprotection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…For example, clinically available HDACi, Hsp inhibitors, and celastrol itself are associated with significant toxicities (42)(43)(44)(45)(46)(47). Our results demonstrate that HDACi and celastrol could have undesirable "off-target" effects that should be identified before clinical trials in GD are pursued (48). Further work is required to determine whether route of administration, dose, molecular structure, or other aspects of these compounds can be selected to maximize therapeutic effect and minimize toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…For example, clinically available HDACi, Hsp inhibitors, and celastrol itself are associated with significant toxicities (42)(43)(44)(45)(46)(47). Our results demonstrate that HDACi and celastrol could have undesirable "off-target" effects that should be identified before clinical trials in GD are pursued (48). Further work is required to determine whether route of administration, dose, molecular structure, or other aspects of these compounds can be selected to maximize therapeutic effect and minimize toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…28 NGF expression may be necessary to promote neuron survival and function post TBI during repair. 29 Similarly, the neuroprotective effects of BDNF have also been demonstrated in animal models of ischemia 30,31 and TBI. 32 BDNF also has a pivotal role in learning and memory.…”
Section: Discussionmentioning
confidence: 95%
“…17,23 Erythropoietin (EPO), a secreted 30-kD glycoprotein, is a multifunctional tissue-protecting agent that exerts antiapoptotic, antiinflammatory, antioxidative, angiogenic, and neurotrophic effects. 7,38 Recently, several investigations have shown that EPO and its analogs provide substantial benefits to rodents after TBI.…”
mentioning
confidence: 99%